Common Cycles and Baltic-Nordic Economic Integration - Hegerty, Scott William (Economics and Business, 2017)
For centuries, Estonia, Latvia, and Lithuania have enjoyed historic and economic ties with their Nordic neighbors in the Baltic Sea region. While the period since 1991 has been one of increased integration with the European Union, trade linkages with Finland and Sweden are particularly strong for Estonia and Latvia, respectively. This study addresses these connections by applying time-series econometric techniques, with the goal of highlighting where regional connections are strongest. Strong Nordic-Baltic linkages, while providing evidence that historical factors are still important, might also suggest that integration with the rest of the EU is relatively weak. Using quarterly data from 1994 to 2014 for Baltic, Nordic, and other partner countries, business cycles are modeled for output, consumption, and investment. Common regional cycles are also extracted via Principal Components Analysis for the three Baltic countries and for the Nordic countries of Denmark, Finland, Norway, and Sweden. Cross-correlation functions are then generated for various cycle pairs to assess whether any are “synchronized.” One key finding is that the Nordic region has two possible consumption cycles that behave in very different ways, suggesting that this region does not behave as a coherent whole. Norway and Denmark drive one cycle, while Sweden and Finland drive the other. Another key result is that each Baltic country behaves differently from one another. While regional differences are quite large - making it harder to describe this as a single “region” at all - Estonia does show significant connections to Finland, its historic and linguistic neighbor.